Molybdenum isotope fractionations between ferromanganese oxides and seawater influenced ancient sedimentary isotopic signatures - Mengchun Cao; Guang-Yi Wei; Feifei Zhang; Xiangwen Ren; Xuefa Shi; Yi-Bo Lin; Tao Li; Sihui Chen; Hong-Fei Ling; Jian Cao (Communications Earth & Environment)
Abstract The use of molybdenum isotopes (δ98Mo) as a paleo-redox proxy requires quantifications of fluxes and isotopic fractionations in each molybdenum sink. However, no systematic tests on δ98Mo variations in different oxic sediments have been made due to limitations of analytical precision and sample number in pioneering studies. Here, we present the δ98Mo data of ferromanganese nodules sampled at various global basins, which exhibit large variations from −0.95‰ to −0.51‰ with appreciable negative correlations between δ98Mo and manganese–iron ratios. Diagenetic nodules, experiencing dissolution and re-precipitation of manganese oxides in marine sediments, have lower δ98Mo by ~0.3‰ and higher molybdenum contents relative to hydrogenetic nodules. We suggest that changes in relative proportions of manganese and iron oxides and early diagenesis of marine sediments likely influence overall molybdenum isotope fractionations in oxic sinks. Hence, evolution of ancient marine manganese and iron cycles can influence sedimentary δ98Mo signatures, especially in low-oxygen Precambrian oceans.